2011
DOI: 10.1542/peds.2010-0192
|View full text |Cite
|
Sign up to set email alerts
|

Tuberous Sclerosis Complex: Diagnostic Challenges, Presenting Symptoms, and Commonly Missed Signs

Abstract: OBJECTIVE: To describe presenting symptoms and signs according to age group in a cohort of 243 patients with tuberous sclerosis complex (TSC) and identify earlier symptoms and signs that did not lead to immediate diagnosis. PATIENTS AND METHODS: We performed a retrospective chart review for 278 patients with TSC who were examined at Children's Hospital Boston in Massachusetts and at the Herscot Center for Tuberous Sclerosis C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

8
77
1
7

Year Published

2013
2013
2020
2020

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 128 publications
(93 citation statements)
references
References 32 publications
8
77
1
7
Order By: Relevance
“…1,2 As a result, tuberous sclerosis complex is believed to affect anywhere from 1 in 5000 to 1 in 10 000 individuals, 3,4 manifesting as a combination of seizures, mental retardation, and facial angiofibromas 5 along with other clinical features. 6,7 Tuberous sclerosis complex most often presents as seizures at the time of diagnosis, 8,9 with the majority of patients refractory to anticonvulsant drugs, making surgical intervention to control seizures a desirable treatment option. [10][11][12][13][14] Surgical intervention to control focal epilepsy in tuberous sclerosis complex patients can be difficult, however, since these patients often have multiple tubers, many of which are nonepileptogenic.…”
mentioning
confidence: 99%
“…1,2 As a result, tuberous sclerosis complex is believed to affect anywhere from 1 in 5000 to 1 in 10 000 individuals, 3,4 manifesting as a combination of seizures, mental retardation, and facial angiofibromas 5 along with other clinical features. 6,7 Tuberous sclerosis complex most often presents as seizures at the time of diagnosis, 8,9 with the majority of patients refractory to anticonvulsant drugs, making surgical intervention to control seizures a desirable treatment option. [10][11][12][13][14] Surgical intervention to control focal epilepsy in tuberous sclerosis complex patients can be difficult, however, since these patients often have multiple tubers, many of which are nonepileptogenic.…”
mentioning
confidence: 99%
“…The MRI revealed that two major diagnostic criteria such as a SEGA and a renal AML, and multiple renal cysts met the diagnostic criteria for TSC [11]. Thus, the diagnosis was confirmed without genomic analysis.…”
Section: Diagnosis Of Tuberous Sclerosis and Autism Spectrum Disordermentioning
confidence: 90%
“…Эпилептические приступы являются пер-вым симптомом приблизительно в 60 % наблюдений, но во многих случаях диагноз устанавливается не сра-зу, даже при наличии и других клинических проявле-ний заболевания [21,60]. Эпилепсия при ТС часто протекает тяжело, и достаточного контроля эпилеп-тических приступов на фоне медикаментозной тера-пии удается достичь менее чем у половины пациентов [13,18,19].…”
Section: том хunclassified